THE INFLUENCE OF SERVICE QUALITY AND PRODUCT QUALITY ON CUSTOMER SATISFACTION THAT IMPLICATIONS ON REPURCHASE INTEREST - Hudaya, Agung; Djumarno, Djumarno; Djubaedah, Siti (Dinasti Publisher, 2021)
The food industry is quite promising for businesses both large and small businesses, quality of service is an aspect that is often used by the business field of food and beverage, related to quality of service, must often associated more with the quality of products, it is thus an aspect that should considered by the company to get customer satisfaction and repurchase interest . This research will be more in-depth about mobile restaurants, or food trucks, because they are much in demand by novice entrepreneurs and are in great demand by fast food customers. This research is a quantitative study conducted to examine the effect of service quality and product quality from food trucks that affect customer satisfaction and repurchase interest by food truck customers. It took 120 respondents in the study who were randomly selected to answer the questionnaire.